Evaluation of the performance of a nutrition rehabilitation centre in a tertiary care hospital in Eastern India - Panda, Mayadhar; Nanda, Sikata; Murmu, Mangala Charan; Giri, Rama Chandra; Debi, Lila Lalantika (International Journal Of Community Medicine And Public Health, 2019)
Background: Severe acute malnutrition (SAM) places extraordinary challenges in the way of survival, growth and development of the child under five years of age. Our aim was to evaluate the functioning and performance of facility based management of SAM children admitted in the nutrition rehabilitation centre (NRC) and to identify the existing bottlenecks in the NRC. Methods: Children above 1 month and less than 5 years of age with severe acute malnutrition were included during the study period. Demographic details of the SAM children, clinical features during admission were recorded. Anthropometric measurements like MUAC, weight, height/length and WHZ scores were taken at admission and compared with the findings at discharge. Statistical analysis: the data after collection, compilation was analysed by SPSS. Results: Majority 277 (78.47%) of them belonged to rural areas. 300 (85%) SAM children were referred by medical officers. Bilateral oedema was recorded in 12 (17.9%) admitted children during 2014-2015, 22 (17.9%) children in 2015-2016 and in 37 (22.7%) children during 2016-2017. There was significant improvement in the mean weight (kg) and mean MUAC (cm) at discharge was in comparison to the weight and MUAC of the children at admission and this difference in increase in the mean weight and MUAC were found to be statistically significant. Conclusions: Implementation of WHO feeding guidelines resulted in adequate weight gain of inpatient malnourished children, however the frontline workers in the community and health care providers of PHCs should be trained and given hands on training for early identification and referral of SAM cases.